PENGEMBANGAN PEMBELAJARAN MODEL DISCOVERY LEARNING BERBANTUAN TIPS POWERPOINT INTERAKTIF PADA MATERI INTERAKSI MAKHLUK HIDUP DENGAN LINGKUNGAN - Jalil, Muhamad (Universitas Muria Kudus, 2016)
One of learning models alternative in the Curriculum 2013 is Discovery Learning (DL).Fact on the field that a teacher has never developed the DL model. The activity and students'knowledge are low. Discovery Learning model encourage students to be active in the discoveryactivities. The media that can help students in communicating their findings were Powerpointmedia. The purpose of this study is to produce and test the validity, practicality, and effectivenesson DL learning tools assisted TPI. The Research used design research and development (R and D).The results showed that the DL learning tools assisted TPI valid, practical, and effective. The toolswere declared valid with good and best categories. The tools were declared practical by gettingpositive response of students, and teacher gave a good response. The tools were declared effectiveby the student activity on both small and wide scale testing class are in the good and bestcategories. There is the influence of DL activity on knowledge. Classical achievement of small andwide scale testing class reach KKM (2,66). Knowledge improvement of small and wide scaletesting class in the middle category.